Medical conditions increasing the risk of chronic thromboembolic pulmonary hypertension - Bonderman, Diana; Jakowitsch, Johannes; Adlbrecht, Christopher; Schemper, Michael; Kyrle, Paul A.; Schönauer, Verena; Exner, Markus; Klepetko, Walter; Kneussl, Meinhard P.; Maurer, Gerald; Lang, Irene (Thrombosis and Haemostasis, 2005)
Chronic thromboembolic pulmonary hypertension (CTEPH) is characterized by organized thromboemboli that obstruct the pulmonary vascular bed. Although CTEPH is a serious complication of acute symptomatic pulmonary embolism in 4% of cases, signs, symptoms and classical risk factors for venous thromboembolism are lacking. The aim of the present study was to identify medical conditions conferring an increased risk of CTEPH. We performed a case-control-study comparing 109 consecutive CTEPH patients to 187 patients with acute pulmonary embolism that was confirmed by a high probability lung scan. Splenectomy (odds ratio=13, 95% CI 2.7–127), ventriculoatrial (VA-) shunt for the treatment of hydrocephalus (odds ratio=13, 95% CI 2.5–129) and chronic inflammatory disorders, such as osteomyelitis and inflammatory bowel disease (IBD, odds ratio=67, 95% CI 7.9–8832) were associated with an increased risk of CTEPH.
Keywords: Pulmonary embolism; clinical / epidemiological studies; acquired coagulation disorders; infection / bacterial; viral